2017
DOI: 10.1080/01677063.2017.1405000
|View full text |Cite
|
Sign up to set email alerts
|

GeneCG15630(fipi) is involved in regulation of the interpulse interval inDrosophilacourtship song

Abstract: To study the central pattern generators functioning, previously we identified genes, whose neurospecific knockdowns led to deviations in the courtship song of Drosophila melanogaster males. Reduced expression of the gene CG15630 caused a decrease in the interpulse interval. To investigate the role of CG15630, which we have called here fipi (factor of interpulse interval), in the courtship song production, at first, we have characterized fipi transcripts and protein (FIPI) in the mutant flies carrying P inserti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 43 publications
0
8
0
5
Order By: Relevance
“…To test the hypothesis that the Laupala QTL 4 region contains one or more homologs of D. melanogaster song candidate genes, we first identified homologs of Drosophila song candidate genes in the L. kohalensis genome using a reciprocal blast strategy. We identified 11 genes in Drosophila with experimentally confirmed effects on mean interpulse interval from two sources: a review yielding six genes (Gleason 2005), and a literature search using two combinations of three search terms, including "Drosophila," "courtship song" and "gene" or "Drosophila," "courtship song" and "genetic," from 2005 to present using Google Scholar, yielding five additional genes (Turner et al 2013;Fedotov et al 2014Fedotov et al , 2018; Table 1). Sequences of these 11 genes were blasted against the L. kohalensis reference genome using tblastx in Blast+ (Camacho et al 2009), and a new Laupala cerasina transcriptome assembled herein (see File S1) was blasted against the D. melanogaster protein database using tblastn at an E-value cutoff of 10.…”
Section: Identification Of D Melanogaster Song Candidate Homologsmentioning
confidence: 99%
See 2 more Smart Citations
“…To test the hypothesis that the Laupala QTL 4 region contains one or more homologs of D. melanogaster song candidate genes, we first identified homologs of Drosophila song candidate genes in the L. kohalensis genome using a reciprocal blast strategy. We identified 11 genes in Drosophila with experimentally confirmed effects on mean interpulse interval from two sources: a review yielding six genes (Gleason 2005), and a literature search using two combinations of three search terms, including "Drosophila," "courtship song" and "gene" or "Drosophila," "courtship song" and "genetic," from 2005 to present using Google Scholar, yielding five additional genes (Turner et al 2013;Fedotov et al 2014Fedotov et al , 2018; Table 1). Sequences of these 11 genes were blasted against the L. kohalensis reference genome using tblastx in Blast+ (Camacho et al 2009), and a new Laupala cerasina transcriptome assembled herein (see File S1) was blasted against the D. melanogaster protein database using tblastn at an E-value cutoff of 10.…”
Section: Identification Of D Melanogaster Song Candidate Homologsmentioning
confidence: 99%
“…However, the causal genes underlying natural variation remain elusive in most cases. Eleven candidate genes that regulate interpulse interval in Drosophila melanogaster, including ion channel genes, transcription factors, and transcription/translation regulators, have been identified through experimentally generated mutations [reviewed by Gleason (2005), also see Turner et al (2013) and Fedotov et al (2014Fedotov et al ( , 2018]. These discoveries offer insight into the types of genes capable of modulating song rhythmicity in naturally occurring systems and thus are reasonable candidate genes for interspecific variation in other singing insects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we also found a significant overlap between the genes with SNPs significantly associated with environmental variables identified in the North American and the European data sets (SuperExactTest p ‐value <0.05; see Materials and Methods; Table ). Among the 32 significantly overlapping genes, fipi is involved in the Drosophila courtship song (Fedotov et al, 2018) and was associated with variables related to wind in Europe and North America. Courtship song, as well as wind have been shown to activate neurons which are related to the antennal and mechanosensory motor center in the central brain in D .…”
Section: Resultsmentioning
confidence: 99%
“…One such gene from the marginal screen was factor of interpulse interval (fipi), a marginal variant with no significant epistatic interactors. This gene regulates the intervals of courtship song (FEDOTOV et al 2018) and was previously identified in an independent screen for microenvironmental variation (MORGANTE et al 2015). Other courtship-related studies with the DGRP shared genes with robustness in flight performance (CG1358 and Dif) (TURNER .…”
Section: Flight and Courtship Share Morphological Structures And Genementioning
confidence: 94%